Pengaruh Kompetensi Aparatur Desa, Efektivitas Pengendalian Internal, dan Moral Sesitivity terhadap Pencegahan Fraud dalam Pengelolaan Keuangan Desa - Putu Ayu Armelia; Made Arie Wahyuni (Vokasi : Jurnal Riset Akuntansi, 2020)
This study aims to determine the effect of village apparatus competence, effectiveness of internal control, and moral sensitivity on fraud prevention in village financial management in the Banjar District. This study uses a quantitative approach. The research sample consisted of 51 respondents consisting of the village head, treasurer, and the chairman of the Village Consultative Body (BPD) from 17 villages in the Banjar District, determined by the nonprobability..sampling..method, namely purposive sampling. The type of data used is a questionnaire distributed directly to respondents. The data analysis technique used is multiple linear regression analysis and the presentation of data is assisted with the SPSS 22 program for windows. The results of this study indicate that the competence of village officials does not affect fraud prevention in village financial management, the effectiveness of internal control has positive and significante effect on fraud prevention in village financial management and moral sensitivity has a positive and significant effect on fraud prevention in village financial manageme inthe District Banjar Buleleng Regency.